For the love of music : invitations to listening - Steinberg, Michael, 1928-2009 (Oxford University Press, 2006)
The power of music, the way it works on the mind and heart, remains an enticing mystery. Now two noted writers on classical music, Michael Steinberg and Larry Rothe, explore the allure of this melodious art--not in the clinical terms of social scientists--but through stories drawn from their own experience. In For the Love of Music, Steinberg and Rothe draw on a lifetime of listening to, living with, and writing about music, sharing the delights and revelatory encounters they have had with Mozart, Brahms, Stravinsky, and a host of other great (and almost-great) composers. At once highly person.